KEBIJAKAN KEPALA MADRASAH DALAM PENINGKATAN KUALITAS SUMBER DAYA TENAGA PENDIDIK - MULIANI NASUTION; WAHYUDDIN NUR (LP2MTBM MAKARIOZ, 2021)
This study aims to determine and analyze the policies of the Madrasah Principal in Improving the Quality of EducatorResources. Which includes: (1). Formulation of the Head of Madrasah Policy in Improving the Quality of EducatorResources. (2). Implementation of the Head of Madrasah Policy in Improving the Quality of Educator Resources. (3).Evaluation of Madrasah Principals' Policies in Improving the Quality of Educator Resources, In analyzing the data,researchers used qualitative methods. So to get valid data the researchers used data collection techniques by means ofinterviews, observation and documentation. Qualitative analysis with data reduction process, data exposure and conclusiondrawing.